UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI IPA 1 MAN 1 PEKANBARU MELALUI PENERAPAN MODEL LEARNING CYCLE “6E” - Erni Guspita Sari; Sehatta Saragih; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is a class action research that aims to improve the learning process and to increase the student’s mathematics learning outcomes by applying learning cycle “6E”. The subjects of this research are the student of class XI Science I MAN 1 Pekanbaru at first semester of academic years 2015/2016, which amounts to 31 students consist of 13 male and 18 female students with the heterogenous level. This research consists of two cycles, each cycle consists of four stages: planning, implementation, observation, and reflection. The instruments of data collection in this research were observation sheets and students Mathematic tests. The data which collected were analyzed with descriptive analyzed statistically. The action is successful if the scores of teacher’s activities and student’s activities increase in every meeting, improve students’ math achievemsent. From analyzed of teacher and students activity in the learning process showed an improvement of learning process prior to the action on the first and second cycle. The result of this research showed an increasing number of students’ math achievement from the basic score 29 % to 54,8 % on the first daily test and 64,5 % on the second daily test. Based on the result of this research can be concluded that the implentation learning cycle “6E” models can improve students’ math achievemsent at class XI Science I MAN 1 Pekanbaru at first semester of academic years 2015/2016.Key words: Students’ Math Achievement, Learning Cycle “6E”